2014
DOI: 10.1111/1574-6968.12537
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence ofKosakonia radicincitansUMEnt01/12, a bacterium associated with bacterial wilt diseased banana plant

Abstract: Kosakonia radicincitans (formerly known as Enterobacter radicincitans), an endophytic bacterium was isolated from the symptomatic tissues of bacterial wilt diseased banana (Musa spp.) plant in Malaysia. The total genome size of K. radicincitans UMEnt01/12 is 5 783 769 bp with 5463 coding sequences (CDS), 75 tRNAs, and 9 rRNAs. The annotated draft genome of the K. radicincitans UMEnt01/12 strain might shed light on its role as a bacterial wilt-associated bacterium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Previously known as Enterobacter radicincitans , all prior reports of this organism have described it as a plant associated bacteria and have mainly focused on its growth promoting properties (Kampfer et al, 2005; Schreiner et al, 2009; Witzel et al, 2012; Brock et al, 2013; Suhaimi et al, 2014; Bergottini et al, 2015). However, there is a report of K. radicincitans causing bacterial wilt disease in bananas, suggesting its pathogenic potential (Suhaimi et al, 2014). Given the difficulties in accurately identifying organisms previously labeled as part of the Enterobacter genus, we cannot determine whether this is actually the first case of human infection due to K. radicincitans or whether the organism has been previously misidentified, as originally occurred with our isolate.…”
Section: Discussionmentioning
confidence: 99%
“…Previously known as Enterobacter radicincitans , all prior reports of this organism have described it as a plant associated bacteria and have mainly focused on its growth promoting properties (Kampfer et al, 2005; Schreiner et al, 2009; Witzel et al, 2012; Brock et al, 2013; Suhaimi et al, 2014; Bergottini et al, 2015). However, there is a report of K. radicincitans causing bacterial wilt disease in bananas, suggesting its pathogenic potential (Suhaimi et al, 2014). Given the difficulties in accurately identifying organisms previously labeled as part of the Enterobacter genus, we cannot determine whether this is actually the first case of human infection due to K. radicincitans or whether the organism has been previously misidentified, as originally occurred with our isolate.…”
Section: Discussionmentioning
confidence: 99%
“…The assembled genomes were annotated and mapped to the reference genomes (CT18) as previously described ( Ho et al, 2012 ; Yap et al, 2012a ). The tRNA and tmRNA were predicted using Aragorn ( Laslett and Canback, 2004 ) whereas the rRNA was predicted with rRNAMMer ( Lagesen et al, 2007 ), and manually validated as described earlier ( Osama et al, 2012 ; Suhaimi et al, 2014 ). To compare, we have included three reference genomes and six of our own published sequenced genomes (described earlier), representing ST1 (Ty2, P-stx-12, Ty21a, BL196, CR0044) and ST2 populations (CT18, CR0063, UJ308A, UJ816A, ST0208).…”
Section: Methodsmentioning
confidence: 99%
“…It is not yet known which of K. radicincitans genes contribute to the growth improvements observed in inoculated plants; however biochemical tests confirmed that K. radicincitans is diazotrophic (Ruppel and Merbach 1997;Scholz-Seidel and Ruppel 1992). This is also strengthened by genome publications revealing a nitrogenase-encoding nifHDK operon in K. radicincitans strains (Bergottini et al 2015;Mohd Suhaimi et al 2014;Witzel et al 2012) (https://www.ncbi.nlm.nih.gov/nuccore/CP015113.1). Through sequence analysis of the published genomes, we discovered that K. radicincitans DSM16656 T , YD4, UMEnt01/12 and D r a f t GXGL-4A also have an anfHDGK operon encoding an additional nitrogenase.…”
mentioning
confidence: 98%